2017
DOI: 10.5004/dwt.2017.20801
|View full text |Cite
|
Sign up to set email alerts
|

Mixture of illite-kaolinite for efficient water purification: Removal of As(III) from aqueous solutions

Abstract: a b s t r a c tAdsorption technology is one of the most promising technologies to remove heavy metals from water. This paper aims to remove arsenite As(III) from contaminated water using a less costly, easier to handle and efficient absorbent. Purified natural clay was characterized and tested as an adsorbent. Mineralogical and textural analysis showed that this adsorbent is a nonswelling clay mineral (illite + kaolinite) and a mesoporous material with specific surface area S BET = 128 m ). The adsorption equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The results showed that the equilibrium period for removals greater than 96% using biochar 500 o C and greater than 98% using biochar 650 o C was 20 minutes. Increases in the initial availability of free sites may account for the quick increase in the first amount of adsorbed dye [17] .…”
Section: Determine the Equilibrium Timementioning
confidence: 99%
“…The results showed that the equilibrium period for removals greater than 96% using biochar 500 o C and greater than 98% using biochar 650 o C was 20 minutes. Increases in the initial availability of free sites may account for the quick increase in the first amount of adsorbed dye [17] .…”
Section: Determine the Equilibrium Timementioning
confidence: 99%
“…The experimental procedure is identical to that described in our earlier work [4,6]. The amount of CR adsorbed onto IKaol and DDAB-IKaol is determined by the difference between the initial and remaining concentration of CR solution by the following expression:…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
“…Clay minerals exhibit a great potential and prospective as a cost-efficient adsorbent. Many studies have been carried out on the removal of cationic dyes using natural clay minerals [4][5][6]. Their results showed that cationic dyes such as methylene blue (MB) and crystal violet (CV) are more adsorbed by natural clay minerals than are the anionic ones such as CR dye.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these techniques are expensive for developing countries and require skilled labor, hence the need to search for locally available materials to remove arsenic from drinking water. In recent years, local materials like laterite, shale, clay, illite, kaolinite and pozzolan have been used to remove arsenic from the water [11,12,13,14]. Speaking of local materials, natural shale has been used as an adsorbent to remove arsenic from water by Koua-koffi et al [15].…”
Section: Introductionmentioning
confidence: 99%